Aquaculture indicators of young Cherax Quadricarinatus under various feeding plans - Valeriia Zharchynska; Nataliia Hrynevych (Наукові горизонти, 2023)
Aquaculture of crustaceans is one of the main sources of valuable food protein, which cannot be replaced by other animal or vegetable proteins due to its properties. The use of nutritious and balanced feeds in feeding crayfish helps to increase productivity and at the same time obtain ecologically clean and safe products. The research aims to determine the effect of feeding the developed Decapoda fodder. It has been established that feeding Decapoda food contributes to a more intense increase in the size of crayfish. In particular, the increase in length was 1.1±0.1 cm for the period from 90 to 120 days of cultivation and 1.2±0.1 cm for the period from 120 to 150 days. When using Decapoda food, the increase in length of crayfish during the first month of rearing was 1.8 times greater than that of crayfish fed Ancistrus menu. In the growing period from 120 to 150 days, the increase in the length of crayfish in the experimental group was 2.0 times greater, compared with crayfish in the control group for the same period. When crayfish were fed with Decapoda, the intensity of body weight gain was, on average, 1.4 times stronger, compared to control group crabs. At the same time, the survival rate in this group was 74%, which is a 20% higher number of live specimens compared to the control group of crayfish. The results of the study can be used in the development of a technological scheme for the reproduction and cultivation of crayfish